Improving Communication in the Red Meat Industry: Opinion Leaders May Be Used to Inform the Public About Farm Practices and Their Animal Welfare Implications - Munoz, Carolina A.; Hemsworth, Lauren M.; Hemsworth, Paul H.; Rice, Maxine; Coleman, Grahame J. (Frontiers in Psychology, 2022)
Opinion leaders (OLs) within the community may lead debate on animal welfare issues and provide a path for information to their social networks. However, little is known about OLs’ attitudes, activities conducted to express their views about animal welfare and whether they are well informed, or not, about husbandry practices in the red meat industry. This study aimed to 1) identify OLs in the community and among producers and 2) compare OLs and non-OLs’ attitudes, knowledge and actions to express their views about the red meat industry. Two questionnaires, one for the Australian general public (n=501) and one for Australian red meat producers (n=200), were developed to identify general attitudes. From these questionnaires, OLs were identified using a two-step cluster analysis. Subsequently, a sub-sample of 19 OLs (including the public and producers) participated in a follow-up phone interview. Results disclosed some clear OLs’ characteristics. Public OLs held more negative perceptions of the red meat industry and perceived they had more knowledge about husbandry procedures. However, their actual knowledge about animal husbandry was not different from non-OLs. Public OLs also used and trusted social and internet media more than did non-OLs. In the producer group, a large percentage of OLs were identified (64.0% compared to 29.1% in the public group). Producer OLs had more actual knowledge about animal husbandry and engaged in more behaviours to express dissatisfaction with the industry than non-OLs (dissatisfaction in relation to the image of the red meat industry). Unlike the public respondents, this group used conventional media more than social and internet media, and their levels of trust in all kinds of media were low. While there were clear differences, both groups believed that is important to increase communication and educate about farm practices. This may present an opportunity to develop an opinion leader intervention strategy where informed OLs could later disseminate accurate information to their social networks. Further studies should test if sustained and facilitated educational sessions between public and producer OLs can assist in increasing communication, knowledge and perhaps, may assist in achieving convergence of concerns and expectations between both groups